Changing aspirations, cultural models of success, and social mobility in northern Ghana - Wolfram Laube (University of Bonn, Center for Development Research (ZEF), 2015)
In northern Ghana, many young people, but also parents, teachers, and local authorities, believe that formal education and professional careers provide the only effective means for the rural youth to get ahead. This paper shows how aspirations have been historically changing and analyses in how far new career pathways lead to upward social mobility. Results from qualitative and quantitative research show how weak public education and a lack of educational funding as well as employment opportunities frustrate local aspirations and undermine upward social mobility. However, cultural models of personal success based on an interesting mix of local social values and developmental discourses afford the marginalized youth avenues to social recognition and status.
Keywords: 330; Youth; aspirations; education; social mobility; success; cultural change; reciprocity; Ghana